Evaluation of the Effectiveness of Patient-Controlled Epidural Analgesia in Operative Gynecology in Patients with Heart Failure - Valiev Sh.M; Gaziev Z.T. (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Objective: To evaluate the clinical efficacy of patient-controlled epidural analgesia (PCEA) in women with chronic heart failure (CHF) undergoing hysterectomy. Materials and Methods: A prospective randomized study included 40 female patients aged 65–80 years, ASA class III–IV, diagnosed with CHF. Patients were divided into two groups: the control group (n=21) received conventional opioid analgesics as needed, while the study group (n=19) received PCEA with longocaine. Hemodynamic parameters, pain intensity (VAS), cortisol and glucose levels, and incidence of adverse events were assessed. Results: The PCEA group demonstrated significantly lower pain scores, more stable hemodynamic parameters, and statistically significant reductions in cortisol and glucose levels compared to the control group. The incidence of adverse effects was also lower in the PCEA group. Conclusion: PCEA is a safe and effective method for postoperative pain management in gynecological patients with chronic heart failure, providing individualized pain control, hemodynamic stability, and improved postoperative recovery.